PENGEMBANGAN USAHA KECIL MENENGAH DI INDONESIA MELALUI PERAN BANK SYARIAH - Eddy Suratno (Universitas Batanghari, 2017)
Indonesia is one of the countries of the third world countries are categorised are still in the developing stage. In the context of developing countries, the system state economy often rely against capital assistance from outside the country. This has a lotof bearing controversial in a country life order. On the pretext of collaboration withforeign parties in relation to capital assistance to help grow the economy of the country, it was important for this pretext away from the purpose originally, the contraryhas been spoiling the nation own to keep dependent against help-the help is always given by the outside parties to us, so that we can feel the implication itself i.e. the lack of independence of the US to build our own nation. The crisis that hit the nation of Indonesia has had floods in all joints, including the banking sector lives also on view as one trigger, i.e. with credit-credit disalurkannya the wrong target. The crisis proved that the number of small and medium businesses are very much able to survive the crisis facing independently. While the economy has now started shows stretching to bounce back, it seems as if the medium-small business back into oblivion, especially with many entry and operation of foreign businesses – including foreign sales period of post-war banking assets national banking. Islamic banking which has been established since the year 1992 apparently can now be renewed hope for the small and medium enterprise development, especially in the procurement of working capital.Keywords: Islamic Banking, Small Business